Bioactive Self‐Assembled Nanoregulator Enhances Hematoma Resolution and Inhibits Neuroinflammation in the Treatment of Intracerebral Hemorrhage - Wenyan Yu; Chengyuan Che; Yi Yang; Yuzhen Zhao; Junjie Liu; Aibing Chen; Jinjin Shi (Advanced Science)
Abstract Hematoma and secondary neuroinflammation continue to pose a significant challenge in the clinical treatment of intracerebral hemorrhage (ICH). This study describes a nanoregulator formed through the self‐assembly of Mg2+ and signal regulatory protein α (SIRPα) DNAzyme (SDz), aimed at enhancing hematoma resolution and inhibiting neuroinflammation in the treatment of ICH. The structure of SDz collapses in response to the acidic endo/lysosomal microenvironment of microglia, releasing Mg2+ and the SIRPα DNAzyme. The Mg2+ then acts as a cofactor to activate the SIRPα DNAzyme. By blocking the CD47‐SIRPα signaling pathway, microglia can rapidly and effectively phagocytose red blood cells (RBCs), thereby promoting the clearance of the hematoma. Simultaneously, Mg2+ reset the microglia to the M2 phenotype by inhibiting the MYD88/MAPK/NF‐κB signaling pathway, thereby modulating the inflammatory microenvironment of ICH. This co‐delivery and synergistic strategy resulted in a significant reduction in hematoma size, decreasing from 11.90 to 5.84 mm3, and promoted recovery from ICH with minimal systemic side effects. This simple yet highly effective nanoplatform, which involves complex synergistic mechanisms, proves to be effective for ICH therapy and holds great promise for introducing novel perspectives into clinical and translational approaches for ICH.